Luminescent probing of the simplest chiral α‐amino acid–alanine in an enantiopure and racemic state. Issue 7 (3rd May 2017) - Tarasevych, Arkadii V.; Kostyukov, Anton I.; Baronskiy, Mark G.; Rastorguev, Alexander A.; Guillemin, Jean‐Claude; Snytnikov, Valeriy N.
Abstract: Luminescent spectroscopy combined with the technique of luminescent probing with rare earth ions (europium, gadolinium, terbium) and an actinide ion (uranyl) was used to differentiate enantiopure and racemic alanine, the simplest chiral proteinogenic amino acid. Using the achiral luminescent probes, small differences between pure L and DL alanine in the solid state were strongly amplified. Based on the observed electronic transitions of the probes, the position of the triplet level of the coordinated alanine was estimated. Formation of homo‐ and heterochiral complexes between enantiomers of alanine and the metal ions is discussed as a possible mechanism of chiral self‐discrimination. Abstract :